Intensive Supervision Program in New Jersey, 1983-1986 - Pearson, Frank S. ([Verlag nicht ermittelbar], 1990)
These data evaluate the New Jersey Intensive Supervision Program (ISP), a program implemented by the New Jersey Department of Corrections in 1983-1986. The central premise of ISP is that certain felony offenders sentenced to prison can be resentenced to a program of intensive supervision in which they are successfully supervised in the community. The data collection evaluates the impact of ISP on recidivism rates, prison space availability, and cost effectiveness and also assesses the opinions of criminal justice professionals toward the program. In the first file data collected on four types of sentenced felons include education, psychological condition, financial status, substance abuse, prior and follow-up criminal records, earning and payment records, sentence and correctional histories, and case characteristics including sentences, offenses, and other dispositions. The second file presents data on type of criminal justice professional interviewed, opinion scale scores on aspects of ISP, and suggestions for ISP.